A Note on Ring Source over Semi-Infinite Rigid Pipe - TİRYAKİOĞLU, BURHAN (My University, 2019)
In this study, semi-infinite rigid pipe is considered. An analytical solution is presented for the diffraction problem of acoustic waves spreadingfrom a ring source by semi-infinite pipe. Applying the boundary and continuity conditions in conjunction with the Fourier transformtechnique, the boundary value problem is solved analytically. The influence of the problem parameters on the diffraction phenomenon isdisplayed graphically.

Bu çalışmada, yarı sonsuz rijit bir boru ele alınmıştır. Bir halka kaynaktan yayılan akustik dalgaların yarı sonsuz boru ile kırınımı problemi için analitik bir çözüm sunulmuştur. Sınır ve süreklilik koşullarını Fourier dönüşüm tekniği ile birlikte uygulayarak, sınır değer problemi analitik olarak çözülmüştür. Problem parametrelerinin kırınım fenomeni üzerindeki etkisi grafiksel olarak gösterilmiştir.
Yarı Sonsuz Rijit Boru Üzerindeki Halka Kaynak Üzerine Bir Not
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler